2011
DOI: 10.2174/157340611796799203
|View full text |Cite
|
Sign up to set email alerts
|

Targeting SP1 Transcription Factor in Prostate Cancer Therapy

Abstract: Transcription factors are proteins that regulate gene expression by binding to specific DNA sequences within gene promoter regions. Specificity protein (Sp) family transcription factors play a critical role in various cellular processes and have been shown to be associated with tumorigenesis. The Sp family consists of several members that contain a highly conserved DNA-binding domain composed of three zinc fingers at the C-terminus and serine/threonine- and glutamine-rich transactivation domains at the N-termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
98
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 90 publications
1
98
0
Order By: Relevance
“…Sp1 promotes the expression of a number of molecules that positively regulate cell cycles and affects the methylation of the DNA CpG island (36). In numerous tumor tissues, Sp1 expression is high and its activity is positively correlated with the degree of tumor invasion, but negatively correlated with patient prognosis (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Sp1 promotes the expression of a number of molecules that positively regulate cell cycles and affects the methylation of the DNA CpG island (36). In numerous tumor tissues, Sp1 expression is high and its activity is positively correlated with the degree of tumor invasion, but negatively correlated with patient prognosis (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, both MT1-MMP and Sp1 levels were decreased in PC3 cells when PI3K and JNK were inhibited, and MT1-MMP levels were decreased in DU-145 cells when MEK was inhibited. These results suggest Sp1-mediated transcriptional regulation of MT1-MMP in prostate cancer cell lines via differential signalling control [13,37] . Sroka et al [25] additionally considered the relationship between IGF-1R and MT1-MMP in prostate cancer cells and tissues, the expression data for which were discussed earlier.…”
Section: Functions Of Mt-mmps In Prostate Cancer Progression and Metamentioning
confidence: 74%
“…A study by Sankpal et al [37] provides evidence for regulation of MT1-MMP by specificity protein 1 (Sp1). Sp1 is expressed in a number of different cancers, and plays key regulatory roles in processes associated with prostate cancer progression and metastasis.…”
Section: Functions Of Mt-mmps In Prostate Cancer Progression and Metamentioning
confidence: 99%
“…Numerous studies have reported interesting properties of the transcription factor, Sp1, which is overexpressed in various human tumors such as lung, prostate, pancreas, breast and colon cancer, among others (6). Sp1 has been implicated as a target for anti-cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Sp1 is highly expressed in tissues of prostate cancer, breast carcinomas, thyroid cancer, hepatocellular carcinomas, pancreatic cancer, colorectal cancer, gastric cancer and lung cancer when compared to normal tissues or cells (5,6). Previous studies showed that Sp1 plays an important role in carcinogenesis and metastasis of several human tumor types by regulating growth-related signal transduction, cell cycle control molecules, apoptosis, oncogenes, tumor suppressor genes, as well as angiogenesis-related factors (7,8).…”
Section: Introductionmentioning
confidence: 99%